The Eighteenth century woman - Baumon, Suzanne; Burroughs, Jun.; Slobagin, Kathy; Stella, Pamela; ABC Video Enterprises, Inc.; Metropolitan Museum of Art (New York, N.Y.). (Pamela Hill ABC Video Enterprises, 1982)
Looks at an exhibit at New York's Metropolitan Museum of Art entitled the Eighteenth Century woman, a vast collection of costume, accessoriesand jewerly. An object d'art that revealed the unique ways in which fashionable eighteenth century women their presence felt in the society,a rt and politics
VHS
Film editor, Jim Flanagan; Featuring Marisa Berenzon Diana Viceland and Stella Blum.
Keywords: Art -- Exhibitions; fashion -- 18th century; Clothing and dress -- Exhibitions